2022
DOI: 10.2337/dc22-0627
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Recommendations for Remission and Prevention of Diabetes in Asian Indians Based on a Data-Driven Optimization Model: The ICMR-INDIAB National Study

Abstract: OBJECTIVE To derive macronutrient recommendations for remission and prevention of type 2 diabetes (T2D) in Asian Indians using a data-driven optimization approach. RESEARCH DESIGN AND METHODS Dietary, behavioral, and demographic assessments were performed on 18,090 adults participating in the nationally representative, population-based Indian Council of Medical Research–India Diabetes (ICMR-INDIAB) study. Fasting and 2-h post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Evidence suggests that low-carbohydrate diets are effective in the management of diabetes, by significantly reducing body weight and also effectively improving HbA1c, fasting plasma glucose, blood lipid, and insulin resistance [43,44]. In addition, it has been shown that in individuals with diabetes, high-protein diets can significantly decrease HbA1c levels [45], and low-fat intake could improve total cholesterol and LDL cholesterol and lower HDL cholesterol [46]. The ICMR INDIAB national study reported that the total calorie intake was higher in males with newly diagnosed diabetes, while the carbohydrate, protein, and fat intake did not significantly differ by sex [47].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that low-carbohydrate diets are effective in the management of diabetes, by significantly reducing body weight and also effectively improving HbA1c, fasting plasma glucose, blood lipid, and insulin resistance [43,44]. In addition, it has been shown that in individuals with diabetes, high-protein diets can significantly decrease HbA1c levels [45], and low-fat intake could improve total cholesterol and LDL cholesterol and lower HDL cholesterol [46]. The ICMR INDIAB national study reported that the total calorie intake was higher in males with newly diagnosed diabetes, while the carbohydrate, protein, and fat intake did not significantly differ by sex [47].…”
Section: Discussionmentioning
confidence: 99%
“…15 Guidelines call for individualization of meal planning, which is sometimes referred to as “Medical Nutritional Therapy”. Despite this, personalization of dietary plans are generally based upon broad constructs like age, activity level, health status and preferences, and, for all patients, tend to emphasize overall calorie reductions and minimization of carbohydrate, 16 especially added sugars and refined grains, in favor of the consumption of non-starchy vegetables and foods that are high in protein. 32…”
Section: Discussionmentioning
confidence: 99%
“…15 Guidelines call for individualization of meal planning, which is sometimes referred to as "Medical Nutritional Therapy". Despite this, personalization of dietary plans are generally based upon broad constructs like age, activity level, health status and preferences, and, for all patients, tend to emphasize overall calorie reductions and minimization of carbohydrate, 16 especially added sugars and refined grains, in favor of the consumption of non-starchy vegetables and foods that are high in protein. 32 However, emerging data demonstrates that there are marked inter-individual responses to food, 17 attributed to differences in physical activity, 33 gut microbiome, 18,19,34 and genetics 35 including in variations in skeletal glucose transporters related to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the fact that the MPC uses an approximate patient model to compute the insulin infusion and could embed real-time measurements in such computations. The role of an MPC to include aspects such as food influences and physical activity has been proposed in [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%